Expressive Speech Acts Found on the Main Character in Venom: Let there be Carnage Movie - Erika Dwi Kusumawardani; Senowarsito; Fitri Yulianti (ELITE Association Indonesia, 2023)
People as social beings (homo socialist) need to build up a good relationship to others. Broadly, pragmatics concentrates on the meaning of language usage in communication based on the context.The objectives of the study are to expressive speech acts found on the main character in Venom: Let There Be Carnage movie. The language used in Venom:Let There Be Carnage movie is a speech act that people usually use to communicate in modern life. People in their everyday communication are figuring out the performance of speech act.The method used by the writer was descriptive qualitative.The expressive speech acts found on the main character Venom: Let There Be Carnage movie are greeting and apologizing. Keywords:SpeechAct, Expressive,Venom:Let There Be Carnage, Movie